Potential Present and Historical Consciousness: Social Reality, Subject and Project. In memory of Hugo Zemelman Merino (Polis (Santiago), 2018)
The following paper is intended to pay a small tribute to the academic and intellectual work of chilean epistemologist Hugo Zemelman Merino, who died recently. In so doing, the bases of his main contribution to Latin American social epistemology, called «epistemology of present potential and historical consciousness» is exposed. Secondly, we review the socio-historical (a) and sociopolitical (b ) extent of the proposal, as it approaches a dialogue with the social sciences beyond the epistemic and methodological approach. Thirdly, as a closure, we performed a small evaluation of his work, in the light of a reading from a socio-political angle.
Keywords: Zemelman; social reality; present potential; historical consciousness; realization mode; social subjects